Characteristics of patients operated for primary hyperparathyroidism at university hospitals in Türkiye: Differences among Türkiye's geographical regions - Kirdak, Turkay; Canturk, Nuh Zafer; Korun, Nusret; Ocakoglu, Gokhan; Erbil, Yesim; Sayek, Iskender; Yagmur, Yusuf (Korean Surgical Society, 2016)
Purpose: The aim of this study was to define the clinical and laboratory characteristics of patients operated on for primary hyperpatathyroidism (PHPT) at university hospitals in Türkiye, and to investigate the differences in the clinical presentations of the disease between different geographical regions. Methods: Patients operated on for PHPT in the university hospitals of Türkiye were included in the study. The demographic, clinical, and laboratory findings and the operational data of the patients were investigated according to the whole country and to different geographical regions. Comparisons were performed according to whole country and regions. Results: A total of 1,162 cases were included in the study from different regions and 20 university hospitals. The mean age of patients was 52.4 ± 0.38 (mean ± standard error) in the general population of Türkiye. The rates of hypertension, urolithiasis, bone disease and 25-hydroxyvitamin D insufficiency were 35%, 18.6%, 67.6%, and 63%, respectively. The median parathormone (PTH), serum total calcium (Ca+2) and phosphorus value were 220 pg/mL (range, 70-2,500 pg/mL), 11.2 mg/dL (range, 9.5-11.2 mg/dL), and 2.4 mg/dL (range, 1-4.7 mg/dL), respectively. The median size of the adenomas resected was 16 mm (range, 4-70 mm). Significant differences were observed in the clinical and laboratory findings of the patients operated on due to PHPT between different geographical regions of Türkiye (P < 0.05). Conclusion: The clinical and laboratory characteristics of the patients with PHPT in different geographical regions of Türkiye differ. Furthermore, the general findings of the cases in Türkiye give us a hint that the severity of the disease here is somewhere between Eastern and Western countries. Copyright © 2016, the Korean Surgical Society.
Keywords: Parathyroidectomy; Primary hyperparathyroidism; Turkey